Pengaruh Reward dan Punishment Terhadap Kinerja Pegawai Negeri Sipil di Area Terdampak Pintu Tol Serang-Panimbang - Rt Erlina gentari; Deni Sunaryo (Jurnal Manajemen, 2022)
This study aims to determine the effect of giving rewards, punishments on the performance of civil servants in the area affected by the Serang Panimbang Toll Gate Quantitative method with descriptive analysis research is the method used in this study, the sample taken using random sampling is 50 people. The respondents are Civil Servants in the Affected Area of the Serang-Panimbang Toll Gate. The statistical method used is SPSSv 25. The results of data processing from this study can be concluded that there is a significant influence between reward (X1) on performance (Y), there is a significant effect between punishment (X2) on performance (Y), there is a significant effect significantly between reward (X1) and punishment (X2) together on performance (Y)